Peran Metode Bercerita Terhadap Nilai Moral Anak Usia Dini - Mariance Paut; Deterisa Kase; Ariani Liukae; Jelisje Ndolu; Maria Asadama; Apri Laos; Rensi Wadu Netu; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
The development of moral values is an important aspect in shaping the personality of early childhood. The purpose of this study was to determine the effect of storytelling methods on the instilling of moral values in children aged 5-6 years. The method in this study was quantitative. The sampling technique used a purposive sampling method, namely children aged 5-6 years. The respondents of this study were 15 children aged 5-6 years at the Bukit Kasih PAUD in Baumata Barat Village, Taebenu District, Kupang Regency. The data collection technique used an instrument in the form of a moral value observation scale that includes honesty, responsibility, empathy, and mutual respect. The data analysis technique was simple linear regression. The findings found that the storytelling method had a positive and significant effect on the instilling of moral values in children aged 5-6 years by 20.8%, which means that the more effective the use of storytelling methods by presenting interesting characters and plots, the more it can increase children’s understanding and positive moral behavior in everyday life. It is hoped that educators can make the storytelling method a fun learning strategy to optimize the character development of early childhood.